If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -7t = -22 Solving 13 + -7t = -22 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -7t = -22 + -13 Combine like terms: 13 + -13 = 0 0 + -7t = -22 + -13 -7t = -22 + -13 Combine like terms: -22 + -13 = -35 -7t = -35 Divide each side by '-7'. t = 5 Simplifying t = 5
| 20x+4=5(4x+2) | | F(3)=12-6x | | 8m/7/2=-6 | | 10x-y=7x+2 | | -3p/5-6=6 | | 5x+33=8 | | Xy-5x+y-5=0 | | 3x+3x+3x=3x+5 | | 7x+4x+2+9=6x+3+4x | | x*0.35=106245 | | 7y/8=22 | | h(-3)=-3-2 | | 18+2x-(4x^2)=0 | | 8/15=x/25 | | 5√15/5a | | (x+y)dx+(x+y-1)dy=0 | | 8-(4x^2)+2x+10=0 | | 3*2x-2,x= | | -7b-2[3(4-b)-5(2b+1)]= | | 7/8(x-13)=14 | | (x+y)dx+(x-y-2)dy=0 | | -7(n+6)=-37-2n | | -5k-35=5(-6k+3) | | 148=-7(-4r+4)-6r | | 400-3x=200 | | 165=-5(6x+3) | | 3(x+-4)=2x+14 | | 5y-5=3y+17 | | 5/6-11/12 | | P-9/2=2 | | 44=-4(3+b) | | 6x^/9 |